Gandhiism vs. Gandhigiri: the Life and Afterlife of the Mahatma - Makarand R. Paranjape (Indialogs: Spanish Journal of India Studies, 2014)
This paper, which contrasts Rajkumar Hirani’s Lage Raho Munna Bhai (2006) with Richard Attenborough’s Gandhi (1982), is as much a celebration of Bollywood as of Gandhi. It is to the former that the credit for most effectively resurrecting the Mahatma should go, certainly much more so than to Gandhians or academics. For Bollywood literally revives the spirit of Gandhi by showing how irresistibly he continues to haunt India today. Not just in giving us Gandhigiri—a totally new way of doing Gandhi in the world—but in its perceptive representation of the threat that modernity poses to Gandhian thought is Lage Raho Munna Bhai remarkable. What is more, it also draws out the distinction between Gandhi as hallucination and the real afterlife of the Mahatma. The film’s enormous popularity at the box office—it grossed close to a billion rupees—is not just an index of its commercial success, but also proof of the responsive chord it struck in Indian audiences. But it is not just the genius and inventiveness of Bollywood cinema that is demonstrated in the film as much as the persistence and potency of Gandhi’s own ideas, which have the capacity to adapt themselves to unusual circumstances and times. Both Richard Attenborough’s Oscar-winning epic, and Rajkumar Hirani’s Lage Raho Munna Bhai show that Gandhi remains as media-savvy after his death as he was during his life.